Perancangan Strategi Pemasaran Pada Kelompok Pengrajin Bengkel Tanjak Rumah Hitam Menggunakan Metode TOWS - Sri Zuliarni; Niesa Septri Handayani (ABEC Indonesia, 2023)
This study aims to determine the internal and external environmental factors that affect the marketing strategy of Bengkel Tanjak Rumah Hitam Community to find out the marketing alternatives that can be chosen by Bengkel Tanjak Rumah Hitam Community that are suitable for marketing their products. This research was conducted at the Bengkel Tanjak Rumah Hitam Community. The method used in this research is TOWS (threat, opportunity, weakness, and strength) with a qualitative approach. From the results of the study, it is known that the position of the Bengkel Tanjak Rumah Hitam Community has high strength from its internal factors and has high opportunities from its external factors, so the strategy that is suitable for marketing is the S-O (Strength-Opportunity) strategy where the company supports an aggressive strategy, namely seizing existing opportunities by utilizing its strengths